Monitoring the effect of hypoxia in bowel dialysate metabolites levels with online biosensors - Corcoles,EP; Boutelle,MG; Deeba,S; Hanna,GB; Darzi,A (2012 International Conference on Biomedical Engineering Icobe 2012, 2012)
The intestinal tract is one of the main organs that, after hemorrhage or shock, appears to be involved in an ischemic/reperfusion injury. Metabolic substances, such as glucose and lactate are useful measurements for the monitoring of intestinal ischemia, since this provokes variation of intracellular biochemical markers. In order to identify the ischemic/reperfusion mechanism adequately, physiological monitoring of the bowel under a different stress condition is required. Biomarkers were monitored during hypoxic conditions induced in a swine model to investigate the effect of this physiological variable on metabolic rates. Results showed that hypoxia could have different effects on bowel dialysate metabolites levels depending on tissue capabilities. © 2012 IEEE.